Role of Oryza sativa chitinases in disease resistance - Snelling, Jacob Wayne, author; Leach, Jan, advisor; Lapitan, Nora Lyssa V., committee member; Chisholm, Stephen Thomas, 1972-, committee member (Colorado State University. Libraries, 2010)
Plant chitinases have long been implicated in defense responses against invading pests and pathogens. In Oryza sativa cv. Nipponbare (rice), chitinases have been shown to co-localize with disease resistance QTL, and are thought to contribute to a multigenic basal defense response. Previous work has shown that overexpression of several O. sativa class I chitinases resulted in heightened resistance to the fungal pathogens Rhizoctonia solani and Magnaporthe oryzae pv. oryzae. Here, I examined the responses of several O. sativa chitinase classes to the RNAi silencing of two transcriptionally active rice chitinase genes LOC_Os02g39330 and LOC_Os04g41620. Silencing of these genes results in a reduction of expression in several additional rice chitinases, and also shows an increased susceptibility phenotype to fungal rice pathogens R. solani, M. oryzae pv. oryzae, and bacterial rice pathogen Xanthomonas oryzae pv oryzae. The relative amounts of silencing of the individual genes LOC_Os02g39330 or LOC_Os04g41620 were not significantly correlated with disease phenotype. Thus, we conclude that silencing of these target genes altered the expression of other chitinases, and perhaps other defense response genes that were not assayed, and that the combination of altered expression profiles contributed to increased susceptibility to the various pathogens.
Department Head: Thomas Holtzer.